Margaret Bayard Smith papers - Smith, Margaret Bayard, 1778-1844.
Correspondence, diaries, journals, and commonplace books. Chiefly correspondence between Smith and her sisters, Jane Bayard Kirkpatrick and Maria Bayard Boyd, and her husband, journalist and banker Samuel Harrison Smith. Other correspondents include Mary Hering Middleton, A. Emilie Pichon, and Eliza Susan Morton Quincy. Topics covered include presidential elections, the British occupation of Washington in 1814, visits to Monticello, Va., and social life in Washington, D.C.
Microfilm edition available
Microfilm edition produced from originals in Manuscript Division.
Social leader, author, and prominent Washingtonian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Boyd, Maria Bayard, -- 1779-1869 -- Correspondence; Kirkpatrick, Jane Bayard, -- 1772-1851 -- Correspondence; Middleton, Mary Hering -- Correspondence; Pichon, A. Emilie -- Correspondence; Quincy, Eliza Susan Morton, -- 1773-1850 -- Correspondence; Smith, Samuel Harrison, -- 1772-1845 -- Correspondence; Elections -- United States; Presidents -- United States -- Election; Monticello (Va.) -- History; Washington (D.C.) -- History -- War of 1812.; Washington (D.C.) -- Social life and customs; Authors; Social leaders